Total Colectomy with Subtotal Proctocolectomy of High Risk Colorectal Cancer Patients - Ahmed Mohialdeen, Fadhil (Kurdistan Journal of Applied Research, 2018)
Lynch syndrome is known by an early incidence colorectal cancer and comparatively common synchronous and metachronous neoplastic polyps or cancer or both. The aim of the current study to explore the beneficial of prophylactic colectomy in high risk patients with colorectal cancer. The medical records of 42 colorectal patients whom underwent surgery between 2006 and 2017 of the above hospitals diagnosed as colorectal cancer diseases were retrospectively reviewed. A Structured interview questionnaire was used. The questionnaire was including information on Socio- demographic data such as; age, gender, address, occupation and marital status. In addition, data on the presentation of the disease was obtained and data on complications and post-operative outcomes were also recorded. 42 patients were studied and the mean age ±SD of their age were 49.5± (10.2), 52.4% were male and 47.6% were female.76.1 % of the patients present with a bleeding per-rectum,71.4, 66.6, 61.9 present with abdominal pain, change in bowel habit and abdominal pain respectively. Abdominal mass and rectal mass were 11.9 and 9.5, the most common site of cancer was sigmoid, rectum and caecum 26.19, 14.3 and 11.9 respectively. The post-operative outcome was very less among patients, wound infection, seroma, incisional hernia and chest infection (7%, 7%, 4% and 4% respectively. We concluded from the current study that colorectal cancer with the technique of prophylactic total colectomy with or without subtotal proctectomy that increase the survival, decrease the morbidity and make the endoscopic follow –up easier and more comfortable to the patients for short and long follow-up interval.